Performing statistical population reconstruction using Program PopRecon 2.0 - Michael V. Clawson; John R. Skalski; James M. Lady; Christian A. Hagen; Joshua J. Millspaugh; David Budeau; John P. Severson (Wildlife Society Bulletin)
ABSTRACT Statistical population reconstruction develops an integrated likelihood model that incorporates age‐at‐harvest composition, harvest totals, hunter effort, and auxiliary data on survival, harvest, or abundance to model demographics of harvested populations. Each statistical population reconstruction model is handcrafted to account for varying levels of available demographic data, hunting regulations, sampling of the harvest process, and biology of the harvested species. PopRecon 2.0 is a software program that facilitates the creation and analysis of these unique demographic models and capable of analyzing either full or pooled age‐at‐harvest data using either fixed or random effects on the annual survival and harvest processes. The program produces annual estimates of abundance, harvest probabilities, natural survival, and recruitment using a user‐friendly, interactive computing environment and AD Model Builder analytical software. Program PopRecon 2.0 is demonstrated using 23 years (1993–2015) of harvest data on greater sage‐grouse (Centrocercus urophasianus) from Oregon, USA. © 2017 The Wildlife Society.